Market Expectations and Option Prices Techniques and Applications - Mandler, Martin (Physica-Verlag HD, 2003)
This book surveys and summarizes the numerous approaches used to extract information on market expectations from option prices. The various approaches are thoroughly explained and many practical issues are discussed, including: data selection, data preparation, and presentation and interpretation of results. This enables the reader to easily implement these techniques in his own applied work. Most studies concerning uncertainty in financial markets focus on actual uncertainty as represented by historical volatility measures, variances etc. In contrast, using option prices allows us to study uncertainty in expectations, i.e. to take a forward looking perspective. In some applications we study how ECB-council meetings affect uncertainty in money market expectations. Most interesting among our results is a number of event studies which compare how uncertainty in market participants’ expectations reacts to anticipated and unanticipated results of ECB-council meetings
Keywords: Finance, general; Macroeconomics/Monetary Economics//Financial Economics; Econometrics; Statistics for Business, Management, Economics, Finance, Insurance; Finance; Macroeconomics; Statistics; Optionspreistheorie; Rationale Erwartung; Zinsstrukturtheorie; Hochschulschrift